Pengaruh Disiplin Kerja dan Beban Kerja Terhadap Kinerja Pegawai Dengan Kepuasan Kerja Sebagai Variabel Intervening (Studi Kasus Pada Bappeda Provinsi Banten) - Alwi, Arfian; Suhendra, Indra (Jurnal Riset Bisnis dan Manajemen Tirtayasa, 2019)
This research was conducted at Bappeda Banten Provincial Government. The phenomenon that occurs is the performance generated employees have not met the overall performance standards set. This may be influenced by unsuitable discipline and workload, which may impact employee job satisfaction in carrying out its duties and responsibilities as an employee. The purpose of this study was to examine the effect of discipline, workload and job satisfaction on employee performance and job satisfaction as intervening variable. Sample used eighty people, data collected by questionnaire instrument, measurement using likert scale. The developed instrument tests the level of validity with convergent validity and discriminant validity. Estimates of instrument reliability using composite reliability. Data analysis to answer the problem of research and hypothesis test using Structural Equation Modeling (SEM) with Partial Least Square program (PLS). The research findings means that the overall employee performance is influenced by work discipline variables, workload, job satisfaction and the rest by other variables outside the research model. The result of the research indicates that work discipline has a significant positive effect on employee performance, work load has a significant negative effect on employee performance, job satisfaction has a significant positive effect on employee performance, work discipline has a significant positive effect on job satisfaction, workload negatively significant to job satisfaction, job satisfaction successfully mediate the influence of work discipline on employee performance and job satisfaction successfully mediate the effect of workload on employee performance